Excitatory neurotransmitters in brain regions in interictal migraine patients - Jensen Eric; Tully Shannon; Pendse Gautam; Becerra Lino; Prescot Andrew; Hargreaves Richard; Renshaw Perry; Burstein Rami; Borsook David (SAGE Publishing, 2009)
Abstract Objective To examine biochemical differences in the anterior cingulate cortex (ACC) and insula during the interictal phase of migraine patients. We hypothesized that there may be differences in levels of excitatory amino acid neurotransmitters and/or their derivatives in migraine group based on their increased sensitivity to pain. Methods 2D J-resolved proton magnetic resonance spectroscopy (1H-MRS) data were acquired at 4.0 Tesla (T) from the ACC and insula in 10 migraine patients (7 women, 3 men, age 43 ± 11 years) and 8 age gender matched controls (7 women, 3 men, age 41 ± 9 years). Results Standard statistical analyses including analysis of variance (ANOVA) showed no significant metabolite differences between the two subject cohorts in the ACC nor the insula. However, linear discriminant analysis (LDA) introduced a clear separation between subject cohorts based on N-acetyl aspartylglutamate (NAAG) and glutamine (Gln) in the ACC and insula. Conclusion These results are consistent with glutamatergic abnormalities in the ACC and insula in migraine patients during their interictal period compared to healthy controls. An alteration in excitatory amino acid neurotransmitters and their derivatives may be a contributing factor for migraineurs for a decrease in sensitivity for migraine or a consequence of the chronic migraine state. Such findings, if extrapolated to other regions of the brain would offer new opportunities to modulate central system as interictal or preemptive medications in these patients.